Psikoedukasi kesehatan mental keluarga pada wanita dewasa di Kota Prabumulih - Amalia Juniarly; Mardhiyah, Sayang Ajeng; Purnamasari, Ayu; Rachmawati, Rachmawati (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Numerous studies have shown that social relationships, especially family relationships, can have both long and short term effects on a person's mental health. Depending on the nature of this relationship, mental health can be improved or negatively affected, so from the above background to improve family mental health psychoeducation is held. This activity was carried out using lectures / counseling method. Based on the calculation results of the Wilcoxon Signed Rank Test, the Z value obtained is -2.873 with p = 0.004 (p <0.05), so the hypothesis decision is to accept H1 or which means there is a significant difference in mental health knowledge between groups pre-test and post-test. There were 7 participants who scored post-test < pre-test, 25 participants who scored post-test > pre-test and 38 respondents who scored post-test = pre-test. The psychoeducation carried out was quite successful in increasing knowledge about family mental health in adult women in Prabumulih City. Suggestions for further dedication to be able to do role play to be able to see community skills in dealing with families experiencing mental health problems.